IkBζ is a Key Regulator of Tumour Necrosis Factor-a and Interleukin-17A-mediated Induction of Interleukin-36g in Human Keratinocytes - Sofie Kaas Ovesen; Klaus Schulze-Osthoff; Lars Iversen; Claus Johansen (Medical Journals Sweden, 2021)
The interleukin (IL)-36 cytokine family plays an essential role in inflammatory processes in the skin and is implicated in the pathogenesis of psoriasis. This study explored the role of IL-36 in psoriasis and investigated the molecular mechanism involved in tumour necrosis factor-α (TNFα)/IL-17A-mediated IL-36 induction. In human keratinocytes IL-36 expression was strongly upregulated by combined TNFα and IL-17A stimulation. Moreover, IκBζ, encoded by NFKBIZ, was identified as a key regulator required for TNFα/IL-17A-induced IL-36γ expression. TNFα/IL-17A-induced IL-36γ expression also involved the nuclear factor κB (NF-κB), p38 mitogen-activated protein kinase and ERK1/2 signalling pathways. Furthermore, a specific NF-κB DNA-binding site in the promoter region of IL36G responsible for the TNFα/IL-17A-induced IL36G gene expression was identified. Finally, in a cohort of patients with psoriasis receiving anti-IL-17A treatment, a positive correlation was found between the expression of NFKBIZ and IL36G. In conclusion, these data reveal a novel crucial regulatory mechanism by which TNFα and IL-17A regulate IL-36γ expression.